2009
DOI: 10.1007/s10396-009-0248-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound colored image views produced by application of statistical analysis of radio-frequency signals and histological findings in patients with chronic hepatitis C

Abstract: The results suggest that US-Red% is useful for evaluating liver fibrosis stage (F1-3) and the size of nodules in cirrhosis. In addition, visually detecting the acoustic reflectional plane, which increases with progression of disease, as color images will be clinically beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…33,37,38,40,70 Other studies directly eliminated the impact of hepatic steatosis on liver fibrosis evaluation. 34,44 However, the effects of hepatic steatosis on liver fibrosis assessment have not been reported and need to be considered in future work. The liver can be modeled as a collection of acoustic scatterers that interact with ultrasound waves, containing both diffuse scatterers (hepatocytes) and coherent scatterers (portal triads or lobules).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33,37,38,40,70 Other studies directly eliminated the impact of hepatic steatosis on liver fibrosis evaluation. 34,44 However, the effects of hepatic steatosis on liver fibrosis assessment have not been reported and need to be considered in future work. The liver can be modeled as a collection of acoustic scatterers that interact with ultrasound waves, containing both diffuse scatterers (hepatocytes) and coherent scatterers (portal triads or lobules).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Nakajima et al 34 applied ASQ to evaluate liver fibrosis in 65 patients with chronic hepatitis C and without hepatic steatosis (biopsy: F1 = 15, F2 = 16, F3 = 12, and F4 = 22). The results showed that ASQ is feasible for evaluating liver fibrosis stages (F1-F3) and nodule sizes in liver cirrhosis (F4).…”
Section: Asqmentioning
confidence: 99%
See 1 more Smart Citation